Иммуномодулирующая и противоинфекционная композиция - Плотников Е. В. Евгений Владимирович; Журавков С. П. Сергей Петрович; Плотников В. М. Владимир Михайлович; Короткова Е. И. Елена Ивановна
опубл. 27.04.12